Potential use of nitrate reductase as a biomarker for the identification of active and dormant inhibitors of mycobacterium tuberculosis in a THP1 infection model - Sarkar, Sampa; Sarkar, Dhiman (Journal of Biomolecular Screening, 2012)
The development of a macrophage-based, antitubercular high-throughput screening system could expedite discovery programs for identifying novel inhibitors. In this study, the kinetics of nitrate reduction (NR) by Mycobacterium tuberculosis during growth in Thp1 macrophages was found to be almost parallel to viable bacilli count. NR in the culture medium containing 50 mM of nitrate was found to be optimum on the fifth day after infection with M. tuberculosis. The signal-to-noise (S/N) ratio and Z-factor obtained from this macrophage-based assay were 5.4 and 0.965, respectively, which confirms the robustness of the assay protocol. The protocol was further validated by using standard antitubercular inhibitors such as rifampicin, isoniazid, streptomycin, ethambutol, and pyrazinamide, added at their IC90 value, on the day of infection. These inhibitors were not able to kill the bacilli when added to the culture on the fifth day after infection. Interestingly, pentachlorophenol and rifampicin killed the bacilli immediately after addition on the fifth day of infection. Altogether, this assay protocol using M. tuberculosis-infected Thp-1 macrophages provides a novel, cost-efficient, robust, and easy-to-perform screening platform for the identification of both active and hypoxic stage-specific inhibitors against tuberculosis.
Keywords: high-throughput screening; inhibitor; Mycobacterium tuberculosis; nitrate reductase; THP1